Design of Reducing Agent for Sintering of High-Performance Alloyed PM Steels Based on Different Carbon Grades Analysis - Hadhud, Aimn (My University, 2012)
Carbon activity in terms of carbon dissolution and reducing ability plays a major role in final performance of structural PM components. Graphite is the most common carbon source for structural PM components and due to the carbon effect on powder compressibility has to be admixed to the metal powder. The role of admixed graphite besides hardening the material by its diffusion into the pure or pre-alloyed iron particles is the reduction of the surface oxides to provide metal-metal contact between adjacent particles and thus allowing the neck formation to take place. According to the latest experimental data, the carbon starts to be active at high temperature (˃900ºC), after which graphite rapidly dissolves in the metallic matrix. This means that there is a lack of reducing agent at low temperature (700-900˚C) as well as in high temperature range (˃ 1100˚C) when there is no any carbon source left in the pores for reduction of the most stable surface oxides. The aim of this work is to evaluate the carbon activity of different carbon sources in order to design carbon source activity of which can cover required temperature range. This can be obtained by mixing of different carbon sources that are active at different temperatures as well as by modification of the existing grades. Astaloy CrM (Höganäs AB, Sweden) was mixed with different carbon sources of various properties, namely PG25, PG10, F25, F10, KS4 and ENSACO 250 (TIMCAL SA, Switzerland). The mixes were then compacted to the density of ~7 g/cc. Interrupted sintering of compacts was performed in the range of temperatures from 700 until 1120˚C and sintering for 30 min at 1120˚C. Metallographic and fractographic analysis were the main methods to evaluate the carbon activity in this study. The investigation shows that the carbon starts to be active at ~ 900˚C in the case of KS4, F10 and PG10 and they are comparable in terms of the carbon dissolution and reducing ability, while PG25 and F25 are the less active, whereas ENSACO 250 is inactive at this temperature. However, the only carbon source that completely dissolves during heating to 1120 ºC throughout the compacts was ENSACO 250. After sufficient time was given, KS4, F10, PG10 and F25 were completely dissolved while some amount of PG25 remained un-dissolve at this temperature even after sintering for 30 min.
Keywords: Produktion; Hållbar utveckling; Metallurgi och metalliska material; Production; Sustainable Development; Metallurgy and Metallic Materials